AKIBAT HUKUM ATAS PERBEDAAN AGAMA SUAMI ISTRI YANG BERLANGSUNG SETELAH PERKAWINAN - Bagus Utomo Aji (Dinamika, 2022)
ABSTRACTThe background of marriage is something that is considered sacred in a religious teaching and belief. In Indonesia, interfaith marriages are strictly prohibited and delegated to the 5 religions in Indonesia. So regarding the validity of marriage in Law No.1/1947 article 2 paragraph 1. So regarding the validity of interfaith marriages from the perspective of 5 religions in Indonesia, the legal consequences need to be questioned. The formulation of the problem in the paper contains 2 formulations of the problem, the first is how is the legitimacy of interfaith marriages according to Law No. 1 of 1974 concerning marriage? secondly, what is the legal status of husbands and wives of different religions after marriage? and in scientific work, the research method used is of the normative juridical type and the approach used is the statutory, conceptual and case approach. The sources of legal materials used are primary, secondary and tertiary. There are materials collection and analysis techniques.Keywords: Legal Consequences, Legitimacy, Differences in Religion, Marriage.     ABSTRAK Latar belakang perkawinan merupakan sebuah hal yang sangat dianggap sakral dalam suatu ajaran agama dan kepercayaan. Dalam negara indonesia tidak membolehkan perkawinan beda agama secara tegas dan limpahkan kepada 5 agama di indonesia . Sehingga mengenai sebuah keabsahan perkawinan dalam Undang-Undang No.1/1947 pasal 2 ayat  1. Maka terkait keabsahan perkawinan beda agama perspektif  5 agama di negara indonesia perlu di pertanyakan akibat hukumnya. Rumusan masalahnya dalam karya tulis terdapat didalamnya 2 rumusan masalah yang pertama   bagimana keabsahan perkawinan beda agama menurut uu no 1 tahun 1974 tentang perkawinan ? yang kedua bagimana status keabsahan atas suami dan istri yang beda agama setelah perkawinan ? dan dalam karya ilmiah metode penelitian yang dipakai berjenis yuridis normatif serta pendekatan yang digunakan seperti pendekatan perundang-undangan, konseptual dan kasus. Sumber bahan hukum yang digunakan ialah primer, sekunder dan tersier.  Terdapat teknik pengumpulan dan analis bahan.Kata Kunci: Akibat Hukum, Keabsahan, Perbedaan Beda Agama, Perkawinan.